Alternativas de fontes proteicas na alimentação de ruminantes em substituição ao farelo de soja - Eckstein, Everline Inês (2017)
The objective of this study was to evaluate protein sources in the diet of ruminants in substitution of soybean meal, such as: dry distillery grains with solubles, high energy cotton meal and protected livestock urea, in relation to intake and apparent digestibility dry matter and nutrients, milk production, microbial synthesis, blood parameters, ruminal parameters and partial economic viability of the diets. Four Holstein cows were used at 145 ± 25 days of lactation and four Jersey steers with a ruminal cannula, distributed in the experimental design in the Latin square (4x4) with four treatments and four experimental periods with 21 days each. The treatments used were the substitution of soybean meal by dried distillery grains with solubles (DDGS) of corn or high energy cotton meal (HECM) or protected urea (Ur) in the concentrate + soybean meal to meet the animal requirement. There was a difference in the intake of ethereal extract (EE), neutral detergent fiber (NDF), acid detergent fiber (ADF) by the nutrients present in each food, as well as EE digestibility. Corrected milk production showed a difference between treatments, depending on the amount of EE of the food. For the blood parameters, it was different for the values of cholesterol and urea. Ruminal pH had no difference among diets. However, there was only effect for the variable in time, presenting quadratic effect. The behavior of the ammoniacal nitrogen showed interaction with the evaluation times after the feed, only for 2 hours after the feed, obtaining a quadratic effect for the treatment with urea, which was higher than the others, due to the occurrence of better synchronization concentration of the concentrate. Regarding the partial economic viability, the break-even point was obtained in the treatment with DDGS. The different protein sources used, dried distillers grains with solubles, high-energy cottonseed meal and protected livestock urea can substitute soybean meal for ruminant feed.